PENGARUH KUALITAS RELATIONSHIP MARKETING-ORIENTED PROMOTION TERHADAP LOYALITAS PELANGGAN PADA MASKAPAI PENERBANGAN LION AIR DI SURABAYA DAN SIDOARJO - MARIA, WINDA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
Nowadays, the existence of aviation bureau in Indonesia is emerging, so these companies competes to retain existing customers, to acquire new customers and to achieve customers loyalty. Lion Air, a well-known aviation bureau in Indonesia, is one of them. This research is conducted to measure the influence of relationship marketing-oriented promotion, customer satisfaction, customer trust, and their commitment towards customer loyalty. The hypothesis shows that H1: Relationship marketing-oriented promotion is proved to influence customer satisfaction, H2: Relationship marketing-oriented promotion is proved to influence customer trust, H3: Customer satisfaction is proved to influence customer commitment, H4: Customer satisfaction is proved to influence customer loyalty, H5: Customer trust is proved to influence customer commitment, H6: Customer trust isn’t proved to influence customer loyalty, H7: Customer commitment is proved to influence customer loyalty.